2017
DOI: 10.1053/j.jrn.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic Obesity Definitions by Body Composition and Mortality in the Hemodialysis Patients

Abstract: Objective Sarcopenic obesity (SO), a combination of low muscle mass and high fat mass, is considered as risk factor for mortality in general population. It is unclear if SO affects mortality in maintenance hemodialysis (MHD) patients. In this study, we aimed to determine whether body composition as assessed by currently available SO definitions are related to all-cause mortality in MHD subjects. We also examined the impact of applying different definitions on the prevalence of SO in our MHD database. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 25 publications
3
31
1
5
Order By: Relevance
“…Low LTI and high FTI were found in 14.3% of male HD patients and 11.3% of females. These findings were in concordance with previous studies [9,[17][18][19], and confirm that low muscle mass can occur despite fat mass accumulation, a phenomenon called 'sarcopenic obesity'.…”
Section: Discussionsupporting
confidence: 92%
“…Low LTI and high FTI were found in 14.3% of male HD patients and 11.3% of females. These findings were in concordance with previous studies [9,[17][18][19], and confirm that low muscle mass can occur despite fat mass accumulation, a phenomenon called 'sarcopenic obesity'.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies had demonstrated the association between low muscle mass and mortality . Nonetheless, the associations between body composition parameters and dialysis mortality have not been well established . Different definitions of sarcopenic obesity and hypervolaemic status might distort the association.…”
Section: Discussionmentioning
confidence: 99%
“…6,22 Nonetheless, the associations between body composition parameters and dialysis mortality have not been well established. 27 Different definitions of sarcopenic obesity and hypervolaemic status might distort the association. Low muscle mass was associated with chronic inflammation, which was the key factor of protein energy wasting (PEW).…”
Section: Discussionmentioning
confidence: 99%
“…As with the differences in cut points for defining sarcopenia, there are differences in defining sarcopenic obesity [28]. We chose a BMI of ≥30 [14], and found a much lower prevalence of < 3% for all categories of sarcopenia, part from ALM adjusted for BMI, compared to previous reports, with estimates ranging from 12-62% for men and 2-78% for women [29].…”
Section: Dialysis Patients Particularly Haemodialysis Patients Changmentioning
confidence: 92%